An Enhanced Light-weight Proactive Source Routing Protocol using DIFT-BFHS for MANET (International Journal of Engineering and Computer Science, 2018)
A mobile ad hoc network (MANET) is a foundationless wireless communication network with a collection of mobile nodes, these nodes are not lies within the direct transmission range of each other but depend on the intermediate nodes for data transference. In multi hop wireless networking the opportunistic data forwarding related research has drawn much attention. The main reason for opportunistic data forwarding has not been widely utilized in mobile ad hoc networks (MANETs) because of  lack of an effective lightweight proactive routing feature with strong source routing capability. In this research the PSR working is modified by Depth-first iterative-deepening combined with the best first heuristic search to maintain the information of the entire network topology. DIFT-BFHS spanning tree is constructed to maintain the network topology information. Instead of repeatedly updating this information, the updating is made only when modification occur, in network topology through the nodes. This makes the acquaintance node discovery process simple and reduces the routing overhead; therefore the vigor is saved as much as possible.